2010
DOI: 10.4317/medoral.15.e869
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the surgical difficulty in lower third molar extraction

Abstract: The ability to predict the surgical difficulty of lower third molar extraction facilitates the design of treatment plans by minimizing complications and improving the preparation of patients and assistants in terms of the postoperative management of inflammation and pain. The aims of this study were to evaluate the value of panoramic radiographs in predicting lower third molar extraction difficulty and technique and to determine if the experience of the practitioner had any influence on this predictive ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 25 publications
2
35
0
5
Order By: Relevance
“…Second, they might have not wanted to reveal their wrong assessment of the case. If longer operative times were really due to a lower post-graduate technical ability, the high correlation between pre-and postoperative difficulty evaluation might suggest that a careful preliminary analysis of all parameters can be highly predictive of surgical difficulty, although BarreiroTorres et al (18) found little correspondence between pre-and post-surgical difficulty evaluations for maxillofacial surgeons (38,7%), for oral surgeons (45,1%), or for primary care dentists (31,9%). Moreover, first there is not a universal scale for grading surgeon's experi- Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Second, they might have not wanted to reveal their wrong assessment of the case. If longer operative times were really due to a lower post-graduate technical ability, the high correlation between pre-and postoperative difficulty evaluation might suggest that a careful preliminary analysis of all parameters can be highly predictive of surgical difficulty, although BarreiroTorres et al (18) found little correspondence between pre-and post-surgical difficulty evaluations for maxillofacial surgeons (38,7%), for oral surgeons (45,1%), or for primary care dentists (31,9%). Moreover, first there is not a universal scale for grading surgeon's experi- Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Ce taux était similaire à celui retrouvé dans l'étude de Freudlsperger [9]. En revanche, les travaux de Barreiro-Torres [10], de Santamaria [11], de Sedaghatfar [12], de Marzola [13], d'Ardakani [14] et de Guiguimdé [15] montraient une pré-dominance du sexe féminin avec des prévalences variant entre 58 et 73 %.…”
Section: Discussionunclassified
“…The dura on of surgery from incision to last suture was 19,23,24 recorded a er every tooth extrac on.…”
Section: Methodsmentioning
confidence: 99%